Modeling and simulation of a wirelessly-powered thermopneumatic micropump for drug delivery applications - Marwan Nafea; Jeevananthan Baliah; Mohamed Sultan Mohamed Ali (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2019)
This paper presents modeling and finite element analysis of a thermopneumatic micropump with a novel design that does not affect the temperature of the working fluid. The micropump is operated by activating a passive wireless heater using wireless power transfer when the magnetic field is tuned to match the resonant frequency of the heater. The heater is responsible for heating an air-heating chamber that is connected to a loading reservoir through a microdiffuser element. The solution inside the reservoir is pumped through a microchannel that ends with an outlet hole. The thermal and pumping performances of the micropump are analyzed using finite element method over a low range of Reynold’s number ⩽ 10 that is suitable for various biomedical applications. The results demonstrate promising performance with a maximum flow rate of ∼2.86 μL/min at a chamber temperature of 42.5 ºC, and a maximum pumping pressure of 406.5 Pa. The results show that the developed device can be potentially implemented in various biomedical areas, such as implantable drug delivery applications.